The GAENE—Generalized Acceptance of EvolutioN Evaluation: Development of a new measure of evolution acceptance. Issue 9 (16th June 2016) - Smith, Mike U.; Snyder, Scott W.; Devereaux, Randolph S.
Abstract: The present study reports the development of a brief, quantitative, web‐based, psychometrically sound measure—the Generalized Acceptance of EvolutioN Evaluation (GAENE, pronounced "gene") in a format that is useful in large and small groups, in research, and in classroom settings. The measure was designed to measure only evolution acceptance—not related knowledge or religious beliefs. Item development was based on extensive student interviews and pretesting followed by multiple rounds of qualitative review and quantitative validity testing based on expert review (Lawshe, 1975) and multiple rounds of item revision, then by reliability testing of over 600 high school (HS) and post‐secondary (PS) students (Study 1, GAENE 1.0). Data analysis strongly supported the reliability and validity of GAENE 1.0, principal components analysis supported a two‐factor solution. All the negatively worded items (and only those items) loaded on the second factor. Rasch analysis also suggested the need for items that would be endorsed at the lower end of the person‐item scale. The negatively worded items were, therefore, reworded as positives, additional items were generated to attract wider endorsement, two additional rounds of qualitative and quantitative expert validation were conducted, and reliability testing was repeated with over 600 HS and PS students (Study 2, GAENE 2.0). Both reliability and validity indices of GAENE 2.0 were strong (Lawshe content validity index = 0.72; Cronbach's alphaHS = 0.940; Cronbach's alphaPS = 0.948; Cronbach's alphacombined = 0.945). Principal components analysis suggests that GAENE 2.0 measures a single factor. Together with Rasch analysis results, these data provide substantial initial evidence to support the validity and psychometric integrity of the GAENE as a measure of the degree to which high school and college students accept the theory of evolution. The rigorous development process can also serve as a model for others interested in measure development. © 2016 Wiley Periodicals, Inc. J Res Sci Teach 53: 1289–1315, 2016